Towards best practices for authorship and research evaluation: Effects of performance metrics and the Leiden Manifesto - de Rijcke, Sarah (Septentrio Conference Series, 2017)
Watch the VIDEO here. New forms of evaluation are reconfiguring science in ways we are only beginning to understand. In this talk, I will address a key challenge in social-scientific research regarding how evaluations are implicated in scientific understandings of the world. I will address how public sector transformations (including a stronger emphasis on national economic goals such as innovation and growth) are introducing highly particular notions of ‘good’ performance and uses of evaluative metrics. Using empirical material and results from recent projects, the talk will reflect on how these trends are affecting knowledge production processes in different fields. I will also suggest ways to think more creatively and responsibly about the affordances of evaluation and indicators in academic settings.